MICROGERAÇÃO DISTRIBUÍDA NAS REDES ELÉTRICAS DA CEMAR: impactos e perspectivas - Brito, Nierbeth Costa (2014)
Distributed Microgeneration has increased its stake in electric participation in various countries of the world, mainly due to government incentives for using renewable energy sources with direct impact on reducing environment damage associated with the production of electricity and for being an opportunity to diversify the sources of electricity generation. After the regulation of the subject by the National Electricity Regulator, there is the expectation of the widespread use of distributed microgeneration in CEMAR electrical grids. This research proposes to identify the main impacts of distributed microgeneration to CEMAR electrical grids and its prospects in order to guide the Direction of distribution company on its way of working in this area. The research is guided in the general study of the subject, the current legislation, applicable regulations and the main sources of energy used in the generation and especially the impacts of the widespread use of this technology in CEMAR electrical grids. The need to prepare the company for this new form of grid operation in the presence of distributed microgeneration.is very important.